Sustainability performance measurement in risk and uncertainty management: An analysis of base of the pyramid supply chain literature - Sadaf Aman; Stefan Seuring; Raja Usman Khalid (Business Strategy and the Environment, 2022)
Risk management in the base of the pyramid (BoP) environment is needed to ensure that firms performance objectives are met. Accordingly, integrating sustainability performance measurement in the supply chain risk management would offer interesting avenues for managing risks in BoP supply chain. Therefore, the paper conceptualizes an intersection between supply chain risk/uncertainty management and sustainable performance measurement. This intersection is then tested by a literature review of 164 BoP SC articles between the years 2000 and 2022. Descriptive, frequency, and correlation analysis identify various risks factors studied in the BoP literature so far, their management strategies and respective performance measures. The findings show a broad strategical aspect of managing SC risks and proffered the tactical or operational level performance measures which along with these practices can manage the related risks. Therefore, their incorporation into the risk management process should be considered. The correlation findings highlight the important role of performance process measures and the impact of these along with the management practices on firm's performance outcomes. The study contributes to supply chain risk and performance management literature by capturing the nexus between BoP and supply chain management.
Keywords: 330; base of the pyramid; performance; supply chain risk management; sustainability performance measurement; sustainable supply chain